In silico identification and characterization of the SNPs in the human ASTL gene and their probable role in female infertility - Suri, Kapali; Rajput, Neha; Sharma, Priya; Omble, Aishwarya D.; Kulkarni, Kiran; Gahlay, Gagandeep K. (Frontiers in Cell and Developmental Biology, 2023)
Ovastacin (ASTL), a zinc metalloprotease, is released from a fertilized egg during exocytosis of cortical granules which occurs minutes after the sperm and egg fuse. ASTL cleaves ZP2, one of the four primary glycoproteins of human zona pellucida, and this cleavage prevents polyspermy, causes zona pellucida hardening, and also protects the pre-implantation embryo. Any perturbation in the activity of ASTL can thus disturb this process and may lead to infertility without changing the gross morphology of the oocyte. A small amount of ASTL is also released by unfertilized oocytes but its catalytic activity is absent as it is bound by its inhibitor, Fetuin-B (FETUB). Pre-mature release of ASTL when FETUB is absent also causes infertility. To identify and understand the structural and functional effects of deleterious SNPs of ASTL on its interaction with ZP2 and FETUB and hence on fertility, a total of 4,748 SNPs from the dbSNP database were evaluated using a variety of in silico tools. All of the 40 shortlisted nsSNPs were present in the catalytic domain of the protein. Comparison of the wild type with mutants using MutPred2 suggests an alteration in the catalytic activity/zinc binding site in many SNPs. Docking studies show the involvement of hydrophobic interactions and H bonding between ASTL and ZP2 and also between ASTL and FETUB. Four positions in ASTL involved in the hydrophobic interactions (P-105 and D-200 between ASTL and ZP2; D-198 and L-278 etween ASTL and FETUB) and 5 in H bonding (E-75 and R-159 between ASTL and ZP2; and K-93, R-159, and C-281 between ASTL and FETUB) have SNP's associated with them validating their importance. Interestingly, a cluster of multiple SNPs was found in the motif (DRD200)-D-198, which is also a well-conserved region among several species. Statistical Coupling Analysis (SCA) suggested that the deleterious SNPs were present in the functionally important amino acid positions of ASTL and are evolutionarily coupled. Thus, these results attempt to identify the regions in ASTL, mutations in which can affect its binding with ZP2 or FETUB and cause female infertility.
Keywords: ASTL; female infertility; fertilization; omics; ovastacin; single nucleotide polymorphism